2020
DOI: 10.1186/s12958-020-00660-6
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNAs (lncRNAs) in spermatogenesis and male infertility

Abstract: Background Long non-coding RNAs (lncRNAs) have a size of more than 200 bp and are known to regulate a host of crucial cellular processes like proliferation, differentiation and apoptosis by regulating gene expression. While small noncoding RNAs (ncRNAs) such as miRNAs, siRNAs, Piwi-interacting RNAs have been extensively studied in male germ cell development, the role of lncRNAs in spermatogenesis remains largely unknown. Objective In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 140 publications
3
81
0
1
Order By: Relevance
“…The effect of environmental changes on the altered gene expression are largely implemented by the changes in the epigenome, which further interacts with a networks of DNA methylation reader proteins playing a role in a cascade of gene expression regulation. This assumption led to the identification of a sperm-specific catalogue of transcripts and characterization of gene expression profiles in normal [ 65 , 66 ] and infertile sperm in vertebrates which yielded several promising candidate transcripts that are currently in use as markers of male sperm quality and fertility [ 50 , 62 , 67 , 68 , 69 ]. The methylation changes that occurred in the subvital and aberrant sperm cells at 24 HPS might have been driven by the changes in the gene expression and thus by altered representation of transcripts that could have led to the observed hypermethylation with subsequent deterioration of sperm quality traits and eventual death of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of environmental changes on the altered gene expression are largely implemented by the changes in the epigenome, which further interacts with a networks of DNA methylation reader proteins playing a role in a cascade of gene expression regulation. This assumption led to the identification of a sperm-specific catalogue of transcripts and characterization of gene expression profiles in normal [ 65 , 66 ] and infertile sperm in vertebrates which yielded several promising candidate transcripts that are currently in use as markers of male sperm quality and fertility [ 50 , 62 , 67 , 68 , 69 ]. The methylation changes that occurred in the subvital and aberrant sperm cells at 24 HPS might have been driven by the changes in the gene expression and thus by altered representation of transcripts that could have led to the observed hypermethylation with subsequent deterioration of sperm quality traits and eventual death of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, ASOs can act in the nucleus and intervene in transcription, which makes ASOs widely used in pre-clinical studies of singlegene disorders [56]. The method we established for ASO-mediated testis knockdown in vivo also offers possibility for pre-clinical application of ASOs in humans with regards to male contraception or improvement of reproductive health [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…LINC00467 (ID in NCBI database: 84791), a LncRNA has attracted much attention recently, was reported to be dysregulated in spermatogenesis and male infertility ( 11 , 12 ). Besides, it was also reported that LINC00467 expression was associated with Vogt-Koyanagi-Harada Disease and Behcet’s Disease ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In general, LncRNAs function via interacting with proteins, chromatin DNA or other types of RNAs to mediate their stability or activity in different aspects of tumor biology (7)(8)(9)(10). LINC00467 (ID in NCBI database: 84791), a LncRNA has attracted much attention recently, was reported to be dysregulated in spermatogenesis and male infertility (11,12). Besides, it was also reported that LINC00467 expression was associated with Vogt-Koyanagi-Harada Disease and Behcet's Disease (13).…”
Section: Introductionmentioning
confidence: 99%